Liquidity Risk Management: Ensuring Sustainability And Managing Islamic Banks In The Era Of Banking Industry Development - Riza Arizona; Icha Afrillia Hidayat; Marisa Rizki; Hasrul Zen; Kustia Kustia; Ridwansyah Ridwansyah; Wan Ruslan Abdul Ghani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Liquidity Risk Management is the development of strategies and policies to manage liquidity risks that include the creation of cash reserves, diversification of funding sources, and the use of financial instruments to overcome liquidity shortages. The process of managing risks arising from the inability of an entity (company or bank) to meet its financial obligations on time due to lack of liquidity or available cash funds. Liquidity risk is the risk that a company or individual will be unable to meet short-term financial obligations because it cannot convert its assets into cash. Liquidity risk arises from the inability to meet maturing obligations from cash flow funding sources and/or from high-quality liquid assets that can be pledged, without disrupting the entity's activities and financial condition. Liquidity risk is one of the main challenges faced by companies in the world of finance and business. Liquidity risk can arise in various forms and situations. One of them is the inability of a company to access sufficient cash when needed, which can occur due to factors such as a sudden decline in sales, dependence on short-term funding, or unexpected economic changes. Liquidity instruments can be obtained from collecting third party funds (DPK), lending in the sharia money market, purchasing SBI Syariah, looking for investors from within the country or foreign investors, or from other sources of funds. The results of the study show that the implementation of liquidity risk management in Islamic Banks and UUS is carried out in the form of: 1. The Board of Directors, Commissioners, and DPS (Sharia Supervisory Board) are active in formulating and implementing risk management, 2. Preparing policies, procedures, and setting risk management limits, 3. Carrying out the process of identifying, measuring, monitoring and controlling risks as well as risk management information systems, 4. Forming a comprehensive internal control system.